Analytical research on the determination of a generalized energy efficiency indicator for an energy consumption objects - Nasullo N. Sadullayev1; Mirzoxid O. G‘afurov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Worldwide, including in our Republic, the growing shortage of energy resources is bringing the transition to “green” energy sources to the forefront across all sectors of the national economy. Due to the low cost of energy, energy-intensive and inexpensive products are being widely produced. As a result, Uzbekistan ranks among the leading countries in terms of environmental pollution per unit of product value. Since electricity is mainly produced at thermal power plants, this contributes to a high level of environmental pollution. Although Uzbekistan holds relatively high positions globally in terms of electricity production per capita, the country is still experiencing energy shortages. Given that green energy sources can be assembled and commissioned in a short time, their wide implementation is considered the fastest way to eliminate the energy deficit. However, at present, such sources are mainly being introduced through administrative or mandatory measures, and the results achieved so far cannot be considered sufficient. Analyzing this situation based on the experience of foreign countries and developing technical solutions to address these issues remains a pressing scientific challenge. Aim: Development of a generalized energy efficiency indicator enabling a systematic assessment of the effectiveness of using renewable energy sources at energy consumption facilities, and improvement of the mechanism for expanding green energy based on this indicator. Methods: to analyze international experience and energy efficiency indicators, a correlation analysis is conducted using the Fishburn formula. Results: A system for promoting the use of green energy at energy consumption facilities has been developed based on a generalized efficiency indicator